Oximes Induce Erection and Are Resistant to Oxidative Stress. (16th February 2015) - Pauwels, Bart; Boydens, Charlotte; Brouckaert, Peter; Van de Voorde, Johan
Abstract Introduction Because of their nitric oxide (NO)‐donating capacities, oxime derivatives have shown to offer some therapeutic perspective for the treatment of erectile dysfunction (ED) as well as cardiovascular diseases. However, to date the in vivo effect of these oximes on erectile function remains unknown. In many disease states oxidative stress occurs, impairing NO‐mediated relaxations. Hence the influence of oxidative stress on oxime‐induced effects is also of interest. Aims This study aimed to evaluate the in vivo effect of formaldoxime (FAL) and formamidoxime (FAM) on blood pressure and intracavernosal pressure (ICP); and to examine the role of soluble guanylyl cyclase (sGC) and the influence of oxidative stress on the FAL and FAM responses. Methods Blood pressure and ICP were monitored in vivo after resp. intravenous or intracavernosal injection of FAL and FAM. Moreover isometric tension was measured in vitro on isolated mice corpora cavernosa (CC), thoracic aorta, and femoral artery in organ baths. The role of sGC was investigated using transgenic mice lacking the alpha 1 subunit of sGC. Main Outcome Measures Mean arterial pressure (MAP) and ICP were measured after FAL/FAM injection. In vitro relaxation of CC strips was evaluated in response to addition of FAL/FAM. Results In vivo both FAL and FAM elicit a dose‐dependent lowering of blood pressure (maximal ΔMAP: 33.66 ± 4.07 mm Hg [FAL] and 20.43 ± 2.06 mm Hg [FAM] ) as well as an increase of ICP (maximal increase of ICP/MAP: 70.29 ± 2.88% [FAL] and 52.91 ± 8.61% [FAM] ). The FAL/FAM effect is significantly lower in knockout vs. wild‐type mice. Oxidative stress has an inhibitory effect on corporal NO‐mediated relaxations induced by electrical field stimulation, acetylcholine, and sodium nitroprusside whereas the responses to 8‐(4‐chlorophenylthio)‐guanosine 3′, 5′‐cyclic monophosphate sodium salt, FAL and FAM were not influenced. Conclusions Oximes induce erection which is mediated by sGC. The oxime‐induced relaxations are resistant to oxidative stress, which increases their therapeutic potential for the treatment of ED. Pauwels B, Boydens C, Brouckaert P, and Van de Voorde, J. Oximes Induce Erection and Are Resistant to Oxidative Stress. J Sex Med 2015;12:906–915.